Occupational health conditions and personal protective equipment utilization among women waste workers in Kathmandu: A cross-sectional study - Acharya, Rojina; Sanjay Nath Khanal; Yadav Prasad Joshi; Lal Mani Adhikari; Bhairav Roka (International Journal of Occupational Safety and Health, 2026)
Introduction: Women Waste Workers (WWWs) face significant occupational health risks due to minimal safety practices, limited access to vaccination, and inadequate use of Personal Protective Equipment (PPE). These factors contribute to respiratory diseases, injuries, and musculoskeletal disorders (MSDs). Methods: A cross-sectional study was conducted from February to March 2024 among 90 WWWs in Kathmandu Metropolitan City (wards 10, 12, and 32) using purposive sampling. Data on demographics, work conditions, occupational health status, and PPE use were collected through semi-structured interviews and analyzed using descriptive statistics, Pearson’s chi-square test, and multivariable logistic regression. Results: Most participants were aged 30–40 (47.8%), illiterate (55.6%), and married (87.8%). The majority handled dry waste (61.1%) and worked for ≤7 years (65.6%). Only 12.2% received occupational health and safety (OHS) training. Vaccination rates were low for tetanus (48.9%) and Hepatitis B (28.9%). MSDs (71%) were most common, followed by mental health-related issues (45.6%), skin diseases (42.2%), and respiratory diseases (41.1%). Despite 92.2% reporting PPE use, concerns remain over quality and effectiveness. Multiple binary logistic regression showed that workers earning ≤17,000 rupees had 6.7 times higher odds of skin disease (p = 0.038), while those with >7 years of experience had 85% lower odds (p = 0.002). Visiting a clinic once a year reduced the odds by 90% (p = 0.003), but never visiting showed no significant impact (p = 0.374). Conclusion: Women Waste Workers face severe occupational health risks, highlighting gaps in OHS training, vaccination, health-seeking behavior, and workplace policies. Strengthening OHS programs and improving PPE utilization are essential to protect their health.